Characterisctics of the mitochondrial genome of the roundworm Oscheius myriophila (Rhabditidae) - Pechová, Hana (Jihočeská univerzita, 2017)
Genus Oscheius represents specific group of nematodes which are facultatively entomopathogenic, i.e. they occur in transient stage between necromenic and parasitic life style. Therefore, it represents an interesting model for evolutionary studies; however, the taxonomy of the genus is still not clear. Analysis of the full mitogenome of Oscheius myriophila may help to enhance our knowledge on the selected nematode species with respect to the taxonomy, phylogeny as well as its biology in general.
Characterisctics of the mitochondrial genome of the roundworm Oscheius myriophila (Rhabditidae)
Keywords: mitogenome; entomopathogenic nematodes; phylogenetic reconstruction; mitogenome; entomopathogenic nematodes; phylogenetic reconstruction